Whither jewish music?: jewish studies, music scholarship, and the tilt between seminary and university - Cohen, Judah M. (AJS review, 2008)
In this essay, I explore the history of what has conventionally been described as “Jewish music” research in relation to parallel developments in both ethnomusicology and Jewish studies in the American academic world during the twentieth century. As a case study, I argue, the issues inherent in understanding Jewish music's historical trajectory offer a complex portrait of scholarship that spans the discourses of community, practice, identity, and ideology. Subject to the principles of Wissenschaft since the second half of the nineteenth century, Jewish music study has constantly negotiated the lines between the scholar and practitioner; between the seminary, the conservatory, and the university; between the good of science, the assertion of a coherent Jewish narrative in history, and the perceived need to reconnect an attenuating Jewish populace with its reinvented traditions; and between the core questions of musicology, comparative musicology, theology, and modern ethnomusicology.